Impacts of age and marital status on the elderly's quality of life in an elderly social institution - Susisusanti Daely; Tuti Nuraini; Dewi Gayatri; Hening Pujasari (SAGE Publishing, 2021)
Background: Living a life of good quality is important for everyone. This research aimed to get an overview of the quality of life (QOL) of the elderly in an elderly social institution in Jakarta, Indonesia. Design and Methods: This descriptive study with a cross-sectional design included 107 participants using simple random sampling technique. Data were collected using an abbreviated World Health Organization Quality of Life (WHOQOL-BREF) and analyzed using statistical software, Mann Whitney and Kruskal Wallis test. Results: The mean quality of life of the elderly's was 66.09 (scale: 0-100), with a mean QOL of 67.58 in the physical domain, 66.26 in the psychological domain, 64.64 in the social relationships domain, and 65.88 in the environment domain. Regarding age and marital status, there was a significant difference in the mean QOL of the elderly living in the elderly social institution (p = .017 and .001). In contrast, there was no significant difference in their mean QOL in terms of gender, level of education, and length of stay (p = .323, .164, and .697). Conclusion: The low quality of life of the elderly is our concern. The staff in the elderly social institution could develop some activities for the elderly to increase the elderly's QOL, such as making daily activities plans and the evaluation of those activities.